Manuel Joao Ramos - Isabel Boavida (eds.): The Indigenous and the Foreign in Christian Ethiopian Art – On Portuguese-Ethiopian Contacts in the 16th–17th Centuries. Papers from the Fifth International Conference on the History of Ethiopian Art (Arrabida) - Biasio, Elisabeth (Aethiopica, 2005)
Review